2018
DOI: 10.22190/fueo1803271r
|View full text |Cite
|
Sign up to set email alerts
|

A Time Series Analysis of Four Major Cryptocurrencies

Abstract: Because of increasing interest in cryptocurrency investments, there is a need to quantify their variation over time. Therefore, in this paper we try to answer a few important questions related to a time series of cryptocurrencies. According to our goals and due to market capitalization, here we discuss the daily market price data of four major cryptocurrencies: Bitcoin (BTC), Ethereum (ETH), Ripple (XRP) and Litecoin (LTC). In the first phase, we characterize the daily returns of exchange rates versus the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…These four cryptocurrencies constitute three fourths of the entire market. As reported in Radovanov et al (2018), although correlations vary between these cryptocurrencies, they are fundamentally different from each other because of their unit values, market capitalizations and user applications.…”
Section: Popular Cryptocurrenciesmentioning
confidence: 97%
“…These four cryptocurrencies constitute three fourths of the entire market. As reported in Radovanov et al (2018), although correlations vary between these cryptocurrencies, they are fundamentally different from each other because of their unit values, market capitalizations and user applications.…”
Section: Popular Cryptocurrenciesmentioning
confidence: 97%
“…Nowadays, the cryptocurrency market still has huge potential for growth as governments and corporations worldwide observed that the decentralized nature and blockchain technology could bring benefits. Therefore a lot of research is being conducted for regulated global usage [8]. From this perspective, as the cryptocurrency still has room to grow, we should expect the future growth of many cryptocurrencies, including the XRP.…”
Section: Promising Price Tendencymentioning
confidence: 99%